PERANCANGAN PERANGKAT LUNAK COMPUTER BASE TRAINING PEMBELAJARAN BAHASA JAWA TINGKAT SD (SEKOLAH DASAR) - MY. Teguh Sulistyono; Sudaryanto Sudaryanto (JURNAL DIAN, 2011)
Javanese education computer can help students in understanding the concept and principle material, so the complicated symbol will be easier to learn. The learning process of Javanese either conversation, or Javanese characters will be fun and easy by using this software. The commercial software of Javanese learning is not based on artificial intelligence, called as Computer Based Training. The software of conventional learning consists of the random material which suit to the understanding of the user. This study is aimed at designing software of Computer based training for making learning Javanese easier. This software of Computer Based training candeliver the material of speaking and Javanese characters as a teacher or tutor as the resuft the delivering will be accordance with the students understanding competencies as users. This software will be implemented with the language program of Visual Basic 6.0 which can be operated with Windows operation systems.Keywords : Computer Based Training, Learning Software, artificiat inteltigence, Jayanesse characters.